2011
DOI: 10.1152/japplphysiol.01054.2009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the postcontractile blood-oxygenation-level-dependent (BOLD) effect in skeletal muscle

Abstract: Previous studies show that transient increases in both blood flow and magnetic resonance image signal intensity (SI) occur in human muscle after brief, single contractions, and that the SI increases are threefold larger in physically active compared with sedentary subjects. This study examined the relationship between these transient changes by measuring anterior tibial artery flow (Doppler ultrasound), anterior muscle SI (3T, one-shot echo-planar images, TR/TE = 1,000/35), and muscle blood volume and hemoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
81
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(90 citation statements)
references
References 68 publications
8
81
1
Order By: Relevance
“…also a difference in the biochemical properties of the muscle fibers which may also influence the muscle BOLD signal (14). A recent study has demonstrated that the detected muscle BOLD signal is the result of both blood oxygenation as well as blood volume within the muscle microcirculation (20).…”
Section: Discussionmentioning
confidence: 99%
“…also a difference in the biochemical properties of the muscle fibers which may also influence the muscle BOLD signal (14). A recent study has demonstrated that the detected muscle BOLD signal is the result of both blood oxygenation as well as blood volume within the muscle microcirculation (20).…”
Section: Discussionmentioning
confidence: 99%
“…In the post-hyperemia normalized phase, mB changes reflect a combination of functional changes in muscle oxygen metabolism and venous washout. 18,20 Prolonged normalization may be an additional indication of impaired muscle reperfusion; T 1/2nor was relatively prolonged in smokers, but this did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 96%
“…[18][19][20] We postulate that prolongation of T 1/2peak and TTP in early stage vascular dysfunction leads to decreases in mB peak after compensatory responses have become impaired. In the post-hyperemia normalized phase, mB changes reflect a combination of functional changes in muscle oxygen metabolism and venous washout.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations